Integrated Ownership and Control in the GCC Corporate Sector - Santos, Andre (IMF Working Papers; Working Paper ;, 2015)
The objective of the paper is to assess ownership and control links in the GCC corporate sector. The analysis focuses on the integrated ownership and network arising from ownership data available in Bloomberg and GCC stock exchanges. The paper finds that ownership is concentrated in GCC public sector institutions, holding companies, financial institutions, and family groups. The paper then considers the effect of different definitions of control on the distribution of consolidated debt. Debt concentration is maximized when the wedge between ownership and control is the largest. This is the case when the largest shareholder has at least 5 percent of total shares as defined in Zingales (1994).